Fibrin hydrogels for articular cartilage tissue engineering - Ahmed, Tamer Anwar Esmail (University of Ottawa (Canada), 2010)
Injury of articular cartilage due to trauma or pathological conditions is a major cause of disability worldwide, especially in North America. Due to inadequacies associated with routinely used repair approaches, the orthopaedic community has an increasing tendency to develop biological strategies such as tissue engineering. Tissue-engineered cartilage constructs represent a highly promising treatment option for knee injury as they mimic the biomechanical environment of the native cartilage and have superior integration capabilities. Current tissue engineering techniques utilize any combination of three critical components: a cellular component, a biocompatible and mechanically stable carrier vehicle/matrix scaffold and a bioactive component. Fibrin has been used extensively as a biopolymer scaffold in a variety of tissue engineering application since it combines some important advantages such as high seeding efficiency and uniform cell distribution. In addition, fibrin has adhesion capabilities. Further, it can be produced from the patient's own blood and used as an autologous scaffold without the potential risk of foreign body reaction or infection. We have evaluated the suitability of fibrin as a scaffolding matrix for tissue engineering of articular cartilage. In the first phase, a chondroprogenitor clonal cell line RCJ3.1C5.18 (C5.18) was used in combination with hydrogels from commercial fibrinogen as a model to guide the development of appropriate scaffolds for tissue engineering. However, rapid degradation of fibrin hydrogels was observed after encapsulation of C5.18 cells. Plasmin and matrix metalloproteinases (MMPs) were found to be responsible for fibrin gel breakdown; therefore, approaches to regulate their activity to control gel stability were developed. Aprotinin, a known serine protease inhibitor, and galardin (GM6001), a potent MMP inhibitor, in combination or separately, prevented the breakdown of fibrin--C5.18 hydrogels, whereas only the combination of both promoted the accumulation of extracellular matrix. From this study it was concluded that plasmin and MMPs contribute independently to fibrin hydrogel breakdown, while either enzyme can achieve extracellular matrix breakdown. In order to move this research closer to clinical application, we next evaluated fibrin glue produced by the CryoSealRTM FS System in combination with human bone marrow derived mesenchymal stem cells (hMSCs), since platelet rich fibrin glue can be prepared which releases a wide variety of growth factors upon activation by thrombin. We additionally tested the incorporation of heparin-binding delivery system (HBDS) into these fibrin matrices to immobilize endogenous growth factors as well as exogenous TGF-beta2. HBDS is composed of a bifunctional peptide, heparin and heparin binding growth factors. Strongly CD90+ and CD105+ hMSCs were encapsulated into fibrin (FG) and platelet-rich fibrin (PR-FG) glues with and without HBDS. Encapsulation in PR-FG resulted in a significant increase in collagen II expression at 2.S weeks compared to other glues; however, no difference was detected between FG and PR-FG after 5 weeks. FG resulted initially in increased expression of aggrecan gene. Incorporation of HBDS in PR-FG resulted in lower collagen II gene expression at 2.S weeks. In addition, incorporation of HBDS into either FG or PR-FG did not improve aggrecan gene expression. Both FG and PR-FG glues led to good accumulation of ECM components as indicated by alcian blue staining, while incorporation of HBDS into these glues resulted in slightly lower accumulation of the same ECM components. It was concluded from this study that FG and PR-FG produced by CryosealRTM-FS system are potential scaffolds for tissue engineering of articular cartilage; however, immobilizing growth factors inside fibrin scaffold with the HBDS system does not necessarily result in enhanced expression of the same markers. Our results indicate that stabilization of fibrin is necessary to allow the accumulation of ECM components secreted from the encapsulated cell source. Furthermore, fibrin glue produced by the CryoSeal RTM-FS system is a potential candidate for utilization in tissue engineering of articular cartilage. Further research should be conducted in order to enhance the mechanical properties of fibrin - based constructs and to gain a better understanding of cell signalling involved in chondrogenesis, in order to optimize the conditions for successful fibrin-based strategies to restore damaged articular cartilage.
Keywords: Biology, Molecular.; Engineering, Biomedical.